2006
DOI: 10.5194/acpd-6-9655-2006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arctic smoke – record high air pollution levels in the European Arctic due to agricultural fires in Eastern Europe

Abstract: Abstract. In spring 2006, the European Arctic was abnormally warm, setting new historical temperature records. During this warm period, smoke from agricultural fires in Eastern Europe intruded into the European Arctic and caused the most severe air pollution episodes ever recorded there. This paper confirms that biomass burning (BB) was indeed the source of the observed air pollution, studies the transport of the smoke into the Arctic, and presents an overview of the observations taken during the episode. Fire… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
183
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(190 citation statements)
references
References 55 publications
6
183
1
Order By: Relevance
“…While in earlier studies on Arctic Haze (Rahn, 1981;Barrie, 1986;Yamanouchi et al, 2005;Law and Stohl, 2007) an anthropogenic origin was already shown, several publications during recent years also revealed that biomass burning (as well forest fire as from agricultural origin) is one possibly important constituent of Arctic Haze as well (Warneke et al, 2009;Fu et al, 2009;Stohl et al, 2007). However, so far to our knowledge biomass burning aerosol has overwhelmingly been observed in summer over Spitsbergen or due to agricultural flaming in eastern Europe once in May 2006 .…”
Section: Introductionmentioning
confidence: 83%
“…While in earlier studies on Arctic Haze (Rahn, 1981;Barrie, 1986;Yamanouchi et al, 2005;Law and Stohl, 2007) an anthropogenic origin was already shown, several publications during recent years also revealed that biomass burning (as well forest fire as from agricultural origin) is one possibly important constituent of Arctic Haze as well (Warneke et al, 2009;Fu et al, 2009;Stohl et al, 2007). However, so far to our knowledge biomass burning aerosol has overwhelmingly been observed in summer over Spitsbergen or due to agricultural flaming in eastern Europe once in May 2006 .…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, levoglucosan has also been detected in a number of ambient studies (e.g., Graham et al, 2002;Puxbaum et al, 2006;Feng et al, 2007). The existence of levoglucosan in aerosols in remote marine (e.g., Mochida et al, 2003a) and polar regions (e.g., Stohl et al, 2007) indicates its long-range transport capability. Because levoglucosan is also detected in sediments (Elias et al, 2001) and Antarctic ice (Gambaro et al, 2008), its application to paleo-environmental studies is potentially important, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Turquety et al [2007] used fire perimeter data with large uncertainties (of the order of 50%) with active fire data to derive emissions from boreal forest fires. Stohl et al [2006] in their assertion that record high air pollution was caused by agricultural fires in Eastern Europe assumed that every MODIS active fire detected resulted in a burnt area of 180 hectares. Their assumption was derived from a statistical analysis of boreal forest fires presented by Wotawa et al [2006].…”
Section: Introductionmentioning
confidence: 99%